URBAN TOURISM BETWEEN CONTENT AND ASPIRATION FOR URBAN DEVELOPMENT - Roxana Valentina GÂRBEA (Management & Marketing, 2013)
With excessive urbanization that the society knows today, the city became the place of origin and at the same time a destination for an increasingly number of tourists. Cities have a higher fitting territory, diversity and quality of tourism products coming to fill a reach touristic ground, especially anthropogenic. Urban tourism has seen a significant, but uneven increase, whit the big European cities detaching themselves through cultural richness and tourist valorization of urban space and may be role models for other cities. The article proposes the approach on the concept of urban tourism and how this form of tourism is in full process of affirmation, given that, in recent years many cities search to find a new identity for themselves, to gain international recognition through tourism.